Evaluation of the Expression of SIM and NDM Genes in Pseudomonas Aeruginosa Isolated from Clinical Sources - Dawood, Eilaf Mohammed; Alkazaz, Abdulkareem A. (Iraqi Journal of Science, 2024)
Pseudomonas aeruginosa has recently been labeled a major threat to public health due to its resistance to almost all commonly used antibiotics. Many factors have been suggested for P. aeruginosa's antibiotic resistance. The goal of this study is to find out what role SIM and NDM, which are related to carbapenem resistance, play in P. aeruginosa isolates from local clinical sources. In this study, out of 110 different clinical specimens, 50 were identified as P. aeruginosa from hospitalized patients. All of the isolates were characterized based on the biochemical test and confirmed using the VitekII compact system. P. aeruginosa isolates were tested for antibiotic susceptibility using 8 antibiotics, including: amikacin, tobramycin, ciprofloxacin, levofloxacin, imipenem, meropenem, piperacillin/tazobactam, ticarcillin, and clavulanate. Susceptibility testing results revealed that every isolate was highly resistant to Piperacillin/Tazobactam, with lower resistance to Ticarcillin/clavulanate (TCC). Using the broth dilution method, the minimum inhibitory concentration (MIC) of P. aeruginosa isolates resistant to meropenem ranged from 32µg/100µl to 128 µg/100µl. The EDTA combined disc test was used to detect the ability of P. aeruginosa isolates to produce carbapenemase, and the results showed that all isolates were carbapenemase producers. Additionally, conventional PCR confirmed the identification of P. aeruginosa using 16S. Real-time PCR was adopted to assess the expression of the NDM and SIM genes in 25 of the identified P. aeruginosa isolates. The mean of gene expression results for NDM showed increased expression compared to the control sample of 1.74, while the SIM gene showed expression of 0.95. These genes, SIM and NDM in class B (which are important for resistance in Pseudomonas aeruginosa), result from chromosomal changes that mutate the membrane permeability flow pump, causing excessive expression.